Temporal Dynamics of Cropping Pattern in The Arid Region of Western Rajasthan-A Case Study of Jodhpur District - Kalla, Jagdeesh C; Gajja, B L; Vyas, D L (Annals of Arid Zone, 2016)
Data on land allocation to different crops in Jodhpur district for 21 years (1956.57 to 1976.77) were analysed to examine and quantify the changes in cropping pattern over time by employing Kendall's coefficient of concordance. Despite' attendant temporal variations in climatic', economic, social and technological factors, the changes in cropping pattern have not been perceptible enough. Under the existing circumstances, adoption of new crop technology in the arid areas may not be a viable proposition.